WACANA KEAGAMAAN SYIAH-SUNNI DALAM MAJALAH TEMPO DAN SUARA HIDAYATULLAH - Anshori, Dadang S (LITERA, 2014)
This study aims to describe the language use as representation of mass media attitudes towards Shia-Sunni conflicts. It employed the qualitative method using Fowler’s critical discourse analysis. The data source was news on Shia-Sunni conflicts in Sampang reported in Tempo and Suara Hidayatullah magazines. The findings are as follows. First, Shia-Sunni conflicts are described in news headings and points of view. Tempo describes the conflicts using the point of view of "˜devil attack’ while Suara Hidayatullah presents them as conflicts of religious understanding. Second, expressions such as "˜belief forcing’, "˜Shia cleansing’, "˜devil attack’, and "˜intolerance’ represent Tempo’s attitudes while expressions such as "˜heretical’, "˜misleading’, "˜hijacking’, "˜deifying something’, and "˜infidel’ represent Suara Hidayatullah’s attitudes. Third, based on the use of vocabulary and sentences, Tempo tends to back the Shia group while Suara Hidayatullah tends to back the Sunni group.